The Impact of Digital Financial Services on the Profitability of Agriculture Enterprises A Comparative Study in Indonesia and Hungary - Widjojo Rosita (2021)
The agriculture sector has a significant role to provide for food security in nations, and with the development of technology, digital financial services (DFS) in the agriculture sector can help deision makers to find ways to provide accessibility and efficiency in farming operations. This study intends to fill in the research gap about to what extent DFS could improve profitability of agriculture enterprises in a developed country (Hungary) in contrast to a developing country (Indonesia). The literature review in this study provides the history, structure, definitions and terms used, e.g. agriculture enterprise, DFS, profitability. The methods used in this study are (1) a survey to map DFS in agriculture enterprises, comparing two countries, Indonesia and Hungary, and (2) secondary data analysis to measure the significance of DFS on profitability measures, which are which are revenue, total costs and gross margin, in Indonesia and Hungary. The results from the chi-square test show that most of the variables are significant between countries (Indonesia and Hungary). The result also includes constraints in agriculture development and important features in DFS development. The regression analysis shows that DFS is significant to agriculture enterprises in Hungary but not significant to agriculture enterprises in Indonesia. In conclusion, as DFS in agriculture enterprises in Hungary are widely used through a specific system, a similar system could be applied to Indonesia through agriculture enterprises especially for rural areas where banks are not accessible. There is also an urgent need from agriculture enterprises to provide farmers with education and training to use DFS to facilitate farming transactions.